Effects of lisinopril treatment on the pathophysiology of PCOS and plasminogen activator inhibitor-1 concentrations in rats. Issue 1 (January 2021) - Coskun, Bugra; Ercan, Cihangir M.; Togrul, Cihan; Ozhamam, Esra U.; Coskun, Bora; Eren, Mesut; Vaughan, Douglas E.
Abstract: Research question: Angiotensin-converting enzyme inhibition results in a significant reduction in plasma concentrations of plasminogen activator inhibitor-1 (PAI-1). What are the effects of lisinopril treatment on PAI-1 concentrations and the morphology and function of the ovaries in the letrozole-induced polycystic ovary syndrome (PCOS) rat model? Design: This prospective randomized controlled animal study involved female Wistar albino rats. Twelve rats were assigned as controls (group I). In the study group ( n = 48), letrozole (an aromatase inhibitor) was administered for PCOS modelling for 9 weeks. After confirming disrupted oestrous cycles, the study group was randomized into two groups: group II ( n = 24; letrozole only) and group III ( n = 24; letrozole + lisinopril 15 mg/kg per day). After 12 weeks, each group was divided randomly into two. Biochemical, histopathological and immunohistochemical analyses was performed in subgroups designated A, and fertilization rates were studied in subgroups designated B. Results: Lisinopril treatment reduced the weight and area of the ovaries, the number and wall thickness of cystic follicles, and serum concentrations of LH and testosterone, relative to group II ( P < 0.001). Circulating PAI-1 concentrations were significantly different among three groups (7.7 ± 0.9 ng/ml, 9.8 ± 0.7 ng/ml and 8.6 ± 0.7 ng/ml for groups IA, IIA and IIIA; P < 0.001). Pregnancy rates were 100%, 0% and 16.7% in groups IB, IIB and IIIB. Conclusions: In the letrozole-induced rodent PCOS model, lisinopril modifies the action of letrozole, possibly by inhibition of systemic and ovarian production of PAI-1. The use of PAI-1 inhibitors deserves further investigation in understanding the pathogenesis of PCOS.